Clinical utility of selective molecular genotyping for diagnosis of partial hydatidiform mole; a retrospective study from a regional trophoblastic disease unit. Issue 11 (30th July 2014) - Fisher, Rosemary A; Tommasi, Anna; Short, Dee; Kaur, Baljeet; Seckl, Michael J; Sebire, Neil J
Abstract : Aims: Hydatidiform moles (HMs) are genetically abnormal conceptions, associated with increased risk of gestational trophoblastic neoplasia. Diagnosis is usually based on histopathological criteria but in a minority definitive histological diagnosis is not possible; in such cases molecular genotyping may be diagnostic. This study describes the clinical usefulness of such an approach. Methods: Cases in which central histology review demonstrated abnormal villous morphological features insufficient for definite diagnosis of partial HM (PHM) ('favour PHM' or 'PHM not excluded') underwent molecular genotyping of villous and maternal tissue, using short tandem repeats, to determine ploidy and parental origin of the placental tissue. Results: Of 251 cases with non-diagnostic morphological villous abnormalities, molecular investigation was not possible in 14 (6%; limited material or technical issues). Overall, 124 (49%) were triploid including 71/86 (85%) of those morphologically favouring PHM, and 53/165 (32%) of those favouring non-molar miscarriage. Of 85 cases of triploidy in whom sufficient material was available, 84 had an additional paternal contribution. Single cases of digynic triploidy, tetraploid PHM and two mosaic conceptions were also identified. Twenty-three non-molar diploid cases (21%) exhibited trisomy. Conclusions: Molecular genotyping allows definitive diagnosis of PHM for cases in which specialist histopathology review remains equivocal. While this approach provides definite diagnosis it is considerably more expensive than a pragmatic management approach of human chorionic gonadotrophin surveillance in all such cases.